2003
DOI: 10.1002/jbm.a.10156
|View full text |Cite
|
Sign up to set email alerts
|

Thermally reversible polymer gel for chondrocyte culture

Abstract: We have evaluated a biomaterial to serve as a scaffold for the propagation and amplification of chondrocytes that promotes the original cellular phenotype of these cells. The goal of the present study was to investigate the use of thermally reversible polymer gels poly(NiPAAm-co-AAc), as a biocompatible supporting scaffold for the propagation of chondrocytic cells. The polymer gels at temperatures above its lower critical solution temperature whereas liquefying at temperatures below its lower critical solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 32 publications
2
24
0
Order By: Relevance
“…These results are comparable to those from similar studies reported in the literature (An et al entrapped P 1 chondrocytes from rabbit scapula in a copolymer gel comprising poly(NI-PAM-co-acrylic acid) and reported an increase in cell number of approximately 180 per cent after 28 days [19]. Au et al [47] counted the number of P 3 articular chondrocytes recovered from a poly(NIPAM-co-acrylic acid) hydrogel after 14 days in three-dimensional culture and, in the best case, recorded an increase of 85 per cent. Kwon & Matsuda [48] counted cell numbers in various NIPAM -PEG-NIPAM block-and star-copolymers after culturing for 7 days, finding that none of the materials showed an increase in cell number.…”
Section: 43supporting
confidence: 89%
See 1 more Smart Citation
“…These results are comparable to those from similar studies reported in the literature (An et al entrapped P 1 chondrocytes from rabbit scapula in a copolymer gel comprising poly(NI-PAM-co-acrylic acid) and reported an increase in cell number of approximately 180 per cent after 28 days [19]. Au et al [47] counted the number of P 3 articular chondrocytes recovered from a poly(NIPAM-co-acrylic acid) hydrogel after 14 days in three-dimensional culture and, in the best case, recorded an increase of 85 per cent. Kwon & Matsuda [48] counted cell numbers in various NIPAM -PEG-NIPAM block-and star-copolymers after culturing for 7 days, finding that none of the materials showed an increase in cell number.…”
Section: 43supporting
confidence: 89%
“…Additional challenges arise when the role of biomaterials is extended from that of an extant, 'static' scaffold to one which is required to form an appropriate cell culture material on demand (by responding to a desired stimulus) and in the presence of a population of living cells. The data presented in this work demonstrate that compromises arise when trying to design a material for both the desirable thermoresponsive phase behaviour (LCST) and final material properties (mechanical stability, water content and diffusion) and consideration of other work in the field leads to the same conclusion [19,21,47,48]. Polymer PNS-5.0 from this work underwent a rapid phase-transition at 338C and supported good cell viability and proliferation, yet it was mechanically poor at room temperature owing to a poor temperature tolerance.…”
Section: Discussionmentioning
confidence: 64%
“…Because of its unique nature, PNIPAAm is an attractive biomaterial for tissue engineering applications. PNIPAAm-chitosan (Chen and Cheng 2006); PNIPAAm-acrylic acid (Jasionowski et al 2004) and PNIPAAm-acrylamide (Au et al 2003) copolymers have been used as scaffold material for chondrocyte cultivation and biocompatibility of these materials for future use has been discussed. However, only few studies have been carried out to determine the ability of PNIPAAm to serve as a microcarrier (Kim et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…TG-catalyzed covalent crosslinking occurs via the formation of an amide linkage between the carboxamide and primary amine residues in polymers or polypeptides ( Figure 2.7a) [65]. Sperinde et al first explored the use of TG in hydrogel formation and successful gelation stimulated researchers to study a variety of systems including PEG-peptide or polypeptide hydrogels [7,64,[66][67][68][69]. It was shown that gelation times can be shortened to a few minutes by rationally designing peptide sequences with a significant increase in substrate specificity [69].…”
Section: Crosslinking By Enzymatic Reactionsmentioning
confidence: 99%
“…Sperinde et al first explored the use of TG in hydrogel formation and successful gelation stimulated researchers to study a variety of systems including PEG-peptide or polypeptide hydrogels [7,64,[66][67][68][69]. It was shown that gelation times can be shortened to a few minutes by rationally designing peptide sequences with a significant increase in substrate specificity [69]. In addition, these hydrogels demonstrated good adhesive properties which make them applicable as surgical tissue adhesives [7].…”
Section: Crosslinking By Enzymatic Reactionsmentioning
confidence: 99%